When Minority Labor Migrants Meet the Welfare State - Bernt Bratsberg; Oddbjorn Raaum; Knut Roed (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
The lifecycle employment profiles of minority labor migrants who came to Norway in the early 1970s diverge significantly from those of native comparison persons. During the early years, employment in the migrant group was nearly complete and exceeded that of natives. But, about ten years upon arrival, immigrant employment started a sharp and steady decline, and by 2000 their employment rate was 50 percent, compared to 87 percent for the native comparison group. We find that immigrant employment is particularly sensitive to the business cycle, and that the economic downturns of the 1980s and 1990s accelerated their exit from the labor market. We trace part of the decline to the migrants initially being overrepresented in shrinking industries and occupations. But we also identify considerable disincentives embedded in the social security system that contribute to poor lifecycle employment performance of immigrants with many dependent family members.
Keywords: 330